1996
DOI: 10.1073/pnas.93.17.8999
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of myosin cross bridges by phosphorylation of myosin-binding protein C in cardiac muscle.

Abstract: In addition to the contractile proteins actin and myosin, contractile filaments of striated muscle contain other proteins that are important for regulating the structure and the interaction of the two force-generating proteins. In the thin filaments, troponin and tropomyosin form a Ca-sensitive trigger that activates normal contraction when intracellular Ca is elevated. In the thick filament, there are several myosinbinding proteins whose functions are unclear. Among these is the myosin-binding protein C (MBP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
149
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 23 publications
9
149
3
1
Order By: Relevance
“…Several investigators have proposed that the reduced unloaded shortening velocity in fiber studies is the result of cMyBP-C functioning either as a tether restricting myosin's interactions with actin [15,29,[43][44][45] and/or imparting a viscous load to thick-thin filament sliding [46]. Our data would indicate that neither of these mechanisms can account for the functional effects observed with cMyBP-C in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Several investigators have proposed that the reduced unloaded shortening velocity in fiber studies is the result of cMyBP-C functioning either as a tether restricting myosin's interactions with actin [15,29,[43][44][45] and/or imparting a viscous load to thick-thin filament sliding [46]. Our data would indicate that neither of these mechanisms can account for the functional effects observed with cMyBP-C in this study.…”
Section: Discussionmentioning
confidence: 53%
“…The C-terminal domains of the protein (C7-C10) bind to the myosin thick filament and play a predominantly structural role, 66 while the first four N-terminal domains (designated C0-C1-m-C2 or C0C2) function by regulating the docking of myosin S1 onto actin thin filaments. 67,68 This regulatory action involves C0C2 interacting with actin and with myosin DS2; the latter being the region of myosin S2 that is proximal to the regulatory and essential light chains of the myosin S1 head. Importantly, the phosphoylation of the m-domain, in response to stimuli, is proposed to ''untethers'' the N-terminus of cMyBP-C from myosin DS2 allowing myosin heads to reposition in a conformation that is more favorable for binding actin, thus affecting the rate and force of heart muscle contraction.…”
Section: Cardiac Myosin Binding Protein Cmentioning
confidence: 99%
“…cMyBP-C is the only thick filament protein that is differentially phosphorylated at multiple sites by the enzymes PKA, PKC, and Ca 2Ï© -calmodulin-activated kinase (13). Reconstitution studies showed that PKA-mediated phosphorylation of cMyBP-C extends the cross-bridges from the backbone of the thick filament, changes their orientation, increases the degree of order of the cross-bridges, and decreases cross-bridge flexibility (11). cMyBP-C phosphorylation can change both filament orientation and contractile mechanics (13), but the in vivo role of these posttranslational modifications on whole-organ function remains obscure.…”
mentioning
confidence: 99%
“…Compared with the two skeletal muscle isoforms, the cardiac isoform contains an extra Ig domain at the N terminus (C0), an insertion of 28 residues within the C5 domain, and three potential phosphorylation sites (Ser-273, Ser-282, and Ser-302) that are substrates for cAMP-dependent PKA, Ca 2Ï© -calmodulin-activated kinase, and PKC (8). This region is located between the C1 and C2 domains of the N terminus, which binds to the subfragment 2 (S2) segment of myosin close to the lever arm domain (9)(10)(11), and this interaction may be dynamically regulated by the differential phosphorylation of cMyBP-C (12). cMyBP-C is the only thick filament protein that is differentially phosphorylated at multiple sites by the enzymes PKA, PKC, and Ca 2Ï© -calmodulin-activated kinase (13).…”
mentioning
confidence: 99%